2010
DOI: 10.1007/s12012-010-9062-2
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrogen Compounds Prevent H9c2 Myoblast Oxidative Stress-Induced Mitochondrial Dysfunction and Cell Death

Abstract: Oxidative stress has been connected to various forms of cardiovascular diseases. Previously, we have been investigating the potential of new nitrogen-containing synthetic compounds using a neuronal cell model and different oxidative stress conditions in order to elucidate their potential to ameliorate neurodegenerative diseases. Here, we intended to extend these initial studies and investigate the protective role of four of those new synthetic compounds (FMA4, FMA7, FMA762 and FMA796) against oxidative damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In this study, hydrogen peroxide (H 2 O 2 ) was used to induce apoptosis in H9c2 cells, as it can damage cells by inducing apoptosis and has been used as a well-established model in many studies on cardiovascular disease (Pechtelidou, Beis, & Gaitanaki, 2008;Qi et al, 2010;Ren et al, 2009). The H9c2 rat cardiomyocyte cell line was chosen in the present study, since this cell line retains the characteristics of isolated primary cardiomyocytes and has been considered as a proper model to study molecular responses of the cardiomyocyte to oxidative damage (Silva, Sardão, Coutinho, & Olveira, 2010;Watkins, Borthwick, & Arthur, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hydrogen peroxide (H 2 O 2 ) was used to induce apoptosis in H9c2 cells, as it can damage cells by inducing apoptosis and has been used as a well-established model in many studies on cardiovascular disease (Pechtelidou, Beis, & Gaitanaki, 2008;Qi et al, 2010;Ren et al, 2009). The H9c2 rat cardiomyocyte cell line was chosen in the present study, since this cell line retains the characteristics of isolated primary cardiomyocytes and has been considered as a proper model to study molecular responses of the cardiomyocyte to oxidative damage (Silva, Sardão, Coutinho, & Olveira, 2010;Watkins, Borthwick, & Arthur, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Preventing Caspase 3/7 activation is a strong indicator of anti-apoptotic capacity. Silva et al (2010), among many others have demonstrated that prevention of Caspase-3 activation protects H9C2 cells from apoptosis. GCE prevented Dox from activating Caspase-3/7 robustly and in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of SCs on cell proliferation were assessed by measuring the total cellular protein content by the SRB protein staining assay, as previously described [61], with slight modifications. SRB binds to basic amino acids of cellular proteins and its colorimetric evaluation provides an estimate of total protein mass, which correlates to cell number.…”
Section: Sulforhodamine B (Srb) Assaymentioning
confidence: 99%